Lutjanus synagris (Linnaeus 1758) age-based life history using a multi-model inference approach for growth in the southern Gulf of Mexico - Isabel Cervantes-Camacho; Ximena Renán; Gabriela Galindo-Cortes; Teresa Colás-Marrufo; Virginia Noh-Quiñones; Thierry Brulé (PLoS ONE, 2026)
Lane snapper Lutjanus synagris is an important species that supports both commercial and recreational fisheries. In the southern Gulf of Mexico, lane snapper is one of the snapper species with the highest annual catch volumes. Nevertheless, information on several life-history traits such as longevity, natural mortality and age at maturity is lacking, which are important for providing appropriate management options. From the total captured lane snapper (n = 1150), 367 were used to estimate the age-life history. Specimens were captured through the small-scale fleet of Yucatan from 2008 to 2009 in southern Gulf of Mexico with total lengths from 14.50–45.90 cm and whole weights from 0.05–1.10 kg. Thin otolith sections were used to determine the age of lane snapper. Left sagittae were embedded in clear epoxy resin, thin sectioned (300 µm thickness), and analyzed using a stereomicroscope, counting opaque zones (white) deposited annually during late spring to early summer. Estimated ages ranged from 0 + to 16 years for females (n = 189) and from 0 + to 15 years for males (n = 164). In the growth modeling process, three candidate models were fitted to improve the plausibility of growth estimates under conditions where both small/young and large/old individuals are poorly represented, and the observed length-at-age data show high variability. A Bayesian approach based on the Markov Chain Monte Carlo was used, with informative priors on the growth parameters. During model fitting, three‑parameter versions were used: k, L ∞ , and a third parameter based on length-at-birth, L 0 ; among these, the last two parameters have the same interpretation across all models. The best growth model by sex was selected based on the Leave-one-out cross-validation technique. The von Bertalanffy growth model was the best-fitting model for growth in both females and males. Growth parameters for females were for maximum mean length or asymptotic length ( L ∞ ) = 32.21 cm total length; growth coefficient ( k 1 ) = 0.27 year -1 ; size-at-age-zero ( L 0 ) = 2.06 cm and for males L ∞ =  28.32 cm total length; k 1 =  0.41 year -1 ; L 0 = 2.03 cm. Natural mortality was estimated at 0.39 year -1 for females and 0.41 year -1 for males. Age at maturity in which 50% of the females and males have reached maturity was A 50 = 3.11 years for females and 1.68 years for males. The reference points of the optimal size (L opt ) and optimal age (A opt ) to harvest the specimens to achieve maximum yield were 26.17 cm total length, 6.20 years for females and 21.24 cm total length, 3.38 years for males. These results on the age-based life history and growth of lane snapper are novel for the southern Gulf of Mexico population. This information forms the basis for developing appropriate management measures, as catch volumes and exploitation levels are steadily increasing.